Lifestyles and academic stress among health sciences students at the National University of Chimborazo, Ecuador: a longitudinal study - Salazar-Granizo, Yolanda E.; Hueso-Montoro, César; Caparros-Gonzalez, Rafael A. (Frontiers in Public Health, 2024)
Background: The significant changes experienced by university students in their training are inherent to educational processes. Social isolation caused by the COVID-19 pandemic, online education and the reopening of higher-education institutions produced substantial variations in the lifestyle of university students in health sciences and generated academic stress and perceived stress. This study was conducted at the National University of Chimborazo (UNACH), a public institution located in Riobamba, central Ecuador, the diverse student's population provided an ideal setting for examining the interplay between academic and perceived stress, lifestyle factors, and learning modalities. The research focused on health sciences students across six academic programs. The university's geographical position and demographic characteristics offered a representative sample for investigating these factors within the context changing. Aim: To compare academic and perceived stress and university students' lifestyles at two different periods: 1) during the mandatory social confinement caused by the COVID-19 pandemic with an online learning modality (T1); 2) in the post-pandemic period with a return to face-to-face activities (T2).